Reforming the European Stability and Growth Pact: Public Debt is Not the Only Factor, Private Debt Counts as Well - Gustav A. Horn; Torsten Niechoj; Silke Tober; Till van Treeck; Achim Truger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
Public debt has increased sharply during the financial and economic crisis. The European stability and growth pact could not have prevented this from happening. It follows that the institutional framework of the European Monetary Union is inadequate. Nonetheless, the current debate about reforming the stability and growth pact is dominated by proposals that endorse the one-sided fixation on public deficits and debt and aim to make sanctions more automatic and severe. Such a strategy would not only pose a threat to the current economic recovery in Europe. It also fails to address the problems facing the euro area. Not only public, but also private debt may ptentially destabilize the monetary union. Without a new focus of the pact the problems of the euro area will not be resolved. In this report, the IMK first critically assesses recent reform pro-posals and then presents its own concept of a revised stability and growth pact. Here the focus is on current account balances that may point to unsustainable developments in both the public and the private sector. – – Die Finanz- und Wirtschaftskrise hat einen massiven Anstieg der staatlichen Verschuldung nach sich gezogen, ohne dass der europäische Stabilitäts- und Wachstumspakt dies hätte verhindern können. Es ist offenkundig geworden, dass die bestehenden institutionellen Rahmenbedingungen für die Europäische Währungsunion nicht adäquat sind. In der nun angestoßenen Debatte über den Stabilitäts- und Wachstumspakt dominieren allerdings Reformvorschläge, die die einseitige Fixierung des Paktes auf dieöffentliche Verschuldung fortführen bzw. noch verschärfen würden. Eine solche Strategie würde nicht nur die Erholung der europäischen Wirtschaft belasten, sondern geht zudem an den wirklichen Problemen des Euroraums vorbei. Nicht nur die staatliche Verschuldung ist ein potenzieller Gefahrenherd für die Stabilität der Währungsunion, auch die private. Ohne eine Neuausrichtung des Paktes lassen sich die Probleme des Euroraums dauerhaft nicht überwinden. In diesem Report werden aktuell diskutierte Reformvorschläge kritisch gewürdigt und um ein konkretes Konzept des IMK für einen reformierten Stabilitäts- und Wachstumspakt ergänzt. Dabei liegt der Fokus auf den Leistungsbilanzsalden, die Fehlentwicklungen sowohl im staatlichen als auch im privaten Sektor signalisieren können.
urn:nbn:de:101:1-201202274226
Keywords: 330; Europäischer Stabilitätsmechanismus; Reform; Leistungsbilanz; Schulden; Eurozone